Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1039/a806516k
|View full text |Cite
|
Sign up to set email alerts
|

Critical initial conditions for spontaneous thermal ignition

Abstract: Critical initial conditions for thermal ignition are calculated numerically for planar, cylindrical and spherical geometries. In each case a comparison is made on the bifurcation diagram with the intermediate steady state(s). It is clearly seen that the actual critical initial condition which depends upon the initial temperature proÐle, is partly below the intermediate steady state(s). The variation with ambient temperature, exothermicity and Biot number are all explicitly shown. The results are important for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…For a monotonically decreasing sequence, {µ n } = the wavefront approaches a constant speed from below. Similar features to the case m, n ≥ 1 have been studied for reaction-diffusion systems associated with combustion problems (see, for example, Weber, Balakrishnan, and Wake [18], Gray and Wake [4], and Lacey and Wake [7]). In Figure 8.9 wavefronts with different initial data (u 0 = σ = 0.2, 1, 10) can be seen approaching the same constant speed as t → ∞.…”
Section: Numerical Methods and Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…For a monotonically decreasing sequence, {µ n } = the wavefront approaches a constant speed from below. Similar features to the case m, n ≥ 1 have been studied for reaction-diffusion systems associated with combustion problems (see, for example, Weber, Balakrishnan, and Wake [18], Gray and Wake [4], and Lacey and Wake [7]). In Figure 8.9 wavefronts with different initial data (u 0 = σ = 0.2, 1, 10) can be seen approaching the same constant speed as t → ∞.…”
Section: Numerical Methods and Resultsmentioning
confidence: 64%
“…Matching follows directly giving 18) and the matching condition In particular, as the solution is classical, we require G(η 0 ) = G (η 0 ) = 0.…”
Section: = Nmentioning
confidence: 99%
“…It is intuitively obvious, however, that A C cr would better serve as the parameter of choice in defining the critical threshold since A exhibits a strong dependence on the value of . Previous cursory numerical investigation has supported the basic preceding conclusions [9], and the intent here is to buttress this argument with additional computational results. Specifically, we construct critical threshold curves for all three principal centrosymmetric solids over a wide range of values for λ and .…”
Section: Parametric Surveymentioning
confidence: 63%
“…The distinct advantage, however, is that it can fully account for the initial assembly conditions and is therefore able to provide accurate estimates for the critical initial temperature. Weber et al [9], for instance, recently conducted a limited computational study of the nonstationary model which clearly demonstrated that the practical critical assembly temperature may, under certain circumstances, be 5-10% lower than the critical temperature obtained from steady-state theory. This has profound industrial implications in the assessment of fire hazards and the definition of fire safety standards where a clear distinction must be drawn between the classic "storage" problem, where only steadystate temperatures are important, and the less recognized "assembly" problem, where the initial temperature threshold for self-ignition is of vital concern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation